Countermovement jump performance in elite male and female sprinters and high jumpers - Philpott, L. K.; Forrester, S. E.; van Lopik, K. A.; Hayward, S.; Conway, P. P.; West, A. A. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2021)
Countermovement jumps (CMJs) are widely used in athlete training, performance monitoring and research as an indicator of power output. Despite extensive scientific research on CMJs, data for elite track and field athletes is limited, particularly for non-sprint events and female athletes. The purpose of this study was threefold: (i) to compare CMJ performance between elite sprinters and high jumpers; (ii) to compare CMJ performance between elite male and female athletes in these two events; and (iii) to determine which CMJ take-off parameters correlated most strongly with jump height. Twenty-seven elite athletes (sprinters: nine male and seven female; high jumpers: five male and six female) completed three maximal CMJs. Jump height and take-off phase parameters were obtained from the force-time data and compared between groups; additionally, time series comparisons were performed on the force, power and displacement data. There was no difference in jump height or any of the take-off parameters between the sprinters and high jumpers; however, the time series analysis indicated that the sprinters maintained a lower centre of mass position during the latter concentric phase. The male athletes jumped higher than the female athletes (by 10.0 cm or 24.2%; p < 0.001) with significantly greater body weight normalised peak power (17.9%, p = 0.002) and significantly shorter eccentric time (17.4%, p = 0.035). Jump height was most strongly correlated with peak power. In addition, jump height was also strongly correlated with positive impulse and both minimum and mean concentric centre of mass position. These results support the importance of accounting for event and gender when investigating CMJ performance.